Décimas of the President, an alternative reading of Mister President, by Miguel Ángel Asturias - Solano Ulate, Daniel (2019)
This work gathers the context around the novel book El Señor Presidente(Mister President), published in 1946 by the Guatemalan writer MiguelÁngel Asturias. It briefly looks into History of Guatemala and its State, relevantdetails about president Manuel Estrada Cabrera, and the author’s life.It addresses some general aspects of the novel book, to later refer to specifictopics from my personal view. The paper has the particularity of showing aparallel accompaniment for the reading process. It consists of writing poetryverses according to the chapter structure of the novel, mostly décimas espinelas3as an initial goal. Writing verses seeks to map out, reflect on, describe,or condense relevant aspects about topics, characters, and events. In somecases, difficulties forced me resort to a smaller verse structure called redondilla4.Verses cover two of the three parts of the novel, and resulted in 25décimas and 7 redondillas. They are attached to this work.